Uniting the Different: The Role of Community Leaders in Strengthening Interfaith Religious Moderation - Irzum Farihah; Ismanto Ismanto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to see how the participation of community leaders in Ngargomulyo to strengthen religious moderation in a pluralistic society. This type of research is field research, with data collection techniques through observation and researchers as participant observers, in-depth interviews with non-structured models, and focus group discussions (FGDs). Data analysis uses the Miles Huberman-Saldana model, which begins with data collection which is then sorted first, after which the data is presented, and ends with data verification. The results of this study show that: First, that in uniting communities that are different from faith requires the role of community leaders. This role is carried out in assisting the community, starting from discussion activities between interfaith youth facilitated by the village government. Second, the delivery of religious material, although the target is for residents of the same faith, but still maintain ethics with other religions by not demonising groups that are not of the same faith as themselves. Third, the implementation of community culture that has been passed down from generation to generation becomes a space for encounter between them, so that mechanical solidarity is very visible in these cultural activities.